Geographic context of black‐white disparities in Medicare CAHPS patient experience measures. (23rd November 2018) - Fenton, Anny T.; Burkhart, Q; Weech‐Maldonado, Robert; Haviland, Amelia M.; Dembosky, Jacob W.; Shih, Regina; Wilson‐Frederick, Shondelle M.; Gaillot, Sarah; Elliott, Marc N.
Abstract : Objective: To examine whether black‐white patient experience disparities vary by geography and within‐county contextual factors. Data Sources: 321 300 Medicare beneficiaries responding to the 2015‐2016 Medicare Consumer Assessment of Health care Providers and Systems (MCAHPS) Surveys; 2010 Census data for several within‐county contextual factors. Study Design: Mixed‐effects regression models predicted three MCAHPS patient experience measures for black and white beneficiaries from geographic random effects, contextual fixed effects, and beneficiary‐level case‐mix adjustors. Principal Findings: Black‐white disparities in patient experiences were smaller in counties with higher average patient experiences. Black‐white disparities in patient experiences were not associated with county‐level poverty or racial segregation. However, county racial segregation and some measures of poverty were significantly associated with all beneficiaries' level of health care access. Getting Needed Care scores were higher with greater racial segregation, while Getting Care Quickly scores were lower with higher poverty and racial segregation. Conclusions: Efforts to reduce black‐white disparities in patient experiences should focus on areas with low average patient experiences. Attempts to reduce disparities in timely access to health care should target primarily black, low‐income, and racially and economically segregated areas. Positive associations of racial segregation with accessing needed care were unexpected.